Diseño de un plan de gestión de costo y de tiempo para la administración de proyectos de la empresa constructora Jiménez y Sojo - Mora-Salas, Daniel (Instituto Tecnológico de Costa Rica, 2010)
This project is based on the design of a management plan that includes cost and time for the project administration of the construction company Jiménez & Sojo, company responsible for applying the present project. It is expected to design and implement the best methodology for the subject under discussion, the project management. To achieve this, it was necessary to use the Guide for the Fundamentals of Project Management. Based on it, it was necessary to develop also the range of projects. To accomplish this goal, it was decided to propose a methodology for the three areas in discussion, range, cost and time, using templates and interrelated tools that allow their development. As a final product, it was necessary to develop a manual of procedures in order to initiate, plan and monitor more closely the construction projects that will be developed in the company. It´s concluded that the generation of the above management plan allows companies to develop future construction projects more effectively and with more order in their administration. This is why the referred proposed plan should be viewed as a tool to execute construction projects in a standardized manner to reduce the downside risks and increase the quality and productivity.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Dirección; Procedimiento; Manual; Tiempo; Costo